PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN BANARAN DAN TRUKAN DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , AMANDA PAVITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Practice Of Field Work (PKL) is as graduate prerequirement and get academic title as Ahli Madya in study program Diploma 3 Geomatic Engineering Vocational Education Gadjah Mada University. The purpose Of PKL is to produce Situation Map Scale 1:500 of Banaran and Trukan Orchard Banyuripan Village Bayat Subdistrict Klaten District Central Java Province. The realization of PKL is Begun with the making Of map control framework (KKP). Map control framework are composed from horizontal control framework (KKH) and vertikal control framework (KKV). The Method is used for KKH that is closed poligon, whereas KKV is used leveling method. After KKP is gotten, then did detil measurement. Data of Detil is processed by softwares, there are Surpac, Autocad, and ARCGIS to produce manuscript map. Then the map is tested on site to know the map quality. Last, map is done remedial for fault data. KKH linear accuration is gotten at 1:60771 whereas prerequirement is given at â¤ 1:7500 So KKH had filled the TOR. The Difference level in KKV accuration is gotten total closing difference level at 3 mm, whereas technical spesification that be order at â¤10.449 mm, So KKV had filled the TOR. Meanwhile it is observed by the result of map tested, the each percentage of sampel from Planimetris and elevation must reach 90%. The elevation Sampling that filled the TOR reached 95.24%, so it had filled The TOR. Planimetris Sampling Sampling that filled the TOR reached 88.89%, so it had been not fill The TOR.